Diagnostic yield of a multi-strategy genetic testing procedure in a nationwide cohort of 728 patients with infantile spasms in China. (December 2022) - Liu, Li-Ying; Lu, Qian; Wang, Qiu-Hong; Wang, Yang-Yang; Zhang, Bo; Zou, Li-Ping
Highlights: Infantile spasm (IS) is a common epilepsy syndrome in infancy. A precision genetic diagnosis can conduct further treatment and genetic counseling. We summarized the clinical and genetic information of a cohort of 728 children with IS and established the gene variant spectrum of IS in China. We showed that an appropriate gene testing procedure based on clinical information can ensure a high genetic diagnostic yield. Abstract: Objective: Infantile spasms (IS) is a common epilepsy syndrome in infancy. Genetically based birth defects are among the many causes of infantile spasms. Genetic diagnosis can reveal the etiology of IS and guide treatment strategies and genetic counseling, but significant challenges surround the choice of appropriate genetic diagnostic strategies to improve the diagnostic yield in IS. Methods: For a cohort of Chinese patients with IS, appropriate genetic testing methods were selected according to etiological classification. Methods included karyotyping, copy number variation detection, single-gene sequencing, targeted sequencing panel, and whole-exome sequencing. Results: A total of 728 children with IS from fifteen provinces and municipalities in China from June 2015 to October 2020 were recruited in the study. Among them, 436 were males (59.9%). The median age was 9.46 months. The diagnostic yield of our study was 31.5% (185/587). The top five causative genes were TSC2 ( n = 91), STXBP1 ( n = 21), TSC1 ( n = 15), SCN2A ( n = 6), and CDKL5 ( n = 6). The genetic diagnostic yield was 100% in Down syndrome ( n = 1), neurofibromatosis ( n = 2), and methylmalonic acidemia ( n = 2), 83.5% in tuberous sclerosis complex ( n = 127), and 16.7% in unsolved infantile spasms ( n = 442). Different genetic testing methods for different etiologies show large differences in diagnostic yields. Conclusion: This study demonstrates that appropriate genetic testing procedures for different phenotypes can ensure a high diagnostic yield.